KEMAMPUAN KOMUNIKASI PADA ANAK DENGAN INDIKASI KETERLAMBATAN PERKEMBANGAN KOGNITIF USIA 5-6 TAHUN STUDI KASUS DI RA AZ ZAHRA (DESA SUKARAME KECAMATAN SUKARAME KABUPATEN TASIKMALAYA) - Nurazizah, - (2022)
ABSTRACT This research is based on the importance of early childhood having communication skills according to age level to be able to carry out effective communication activities. Having a well-developed intelligence will help children to easily have communication skills quickly, but what if the intelligence that should be possessed has a delay in its development. So the researchers formulated the problem in the study, namely how the communication skills in children with indications of cognitive development delays aged 5-6 years, both with friends, teachers and parents. -6 years with his friends, teachers and parents. This study uses a qualitative approach with case study research methods. Data collection techniques used are observation, interviews, and documentation. And research data analysis techniques include: data collection, data reduction, data display, and drawing conclusions. The results of observations showed that the communication skills of children with indications of cognitive development delays aged 5-6 years had not developed optimally. Children have not been able to carry out communication activities with their friends optimally. Children have not been able to carry out communication activities with class teachers optimally. Children are able to carry out communication activities with parents optimally. The conclusion is based on the results of the study, the communication skills possessed by children with indications of cognitive development delays aged 5-6 years have not been able to achieve the communication skills that should be possessed by children in that age range, but children are able to have good communication skills when with the closest people. Keywords: communication skills, cognitive development, eraly childhood